Motivational Interviewing and Home Visits to Improve Health Behaviors and Reduce Childhood Obesity: A Pilot Study. (September 2019) - Early, Gayle J.; Cheffer, Natalie D.
Introduction: Childhood obesity prevalence is highest among low-income, Hispanic, and Black children. The purpose of this study was to examine the feasibility of using motivational interviewing (MI) with home visits and the 5-2-1-0 Let's Go! program to improve health behaviors in children. Desirable health behaviors include daily consuming five servings of fruits or vegetables, limiting recreational screen time to 2 hours, exercising for 1 hour, and avoiding sugar-sweetened beverages. Method: Of 68 predominantly Hispanic/Latino participants from three clinic sites, 35 completed the study. One site provided usual care (UC). MI was conducted by a nurse practitioner, reinforced with home or clinic visits. Survey and biometric data were obtained three times over 6 months. Analyses included mean difference of behaviors, and matched pairs t test of initial and final visit behaviors. Results: Health behavior trends improved in both the MI and UC groups; however, more improvement was evident in the MI group. Home visits were appreciated but challenging as the social context of immigration law in 2017 had an unanticipated effect on the study. Conclusions: MI and clinician reinforcement of healthy behaviors may be beneficial for children and families. Home visits cannot be recommended in the undocumented immigrant population at this time.